2021
DOI: 10.3390/ijms222111717
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Metabolism under Different Light Regimes in Wheat

Abstract: Although the relationship between polyamines and photosynthesis has been investigated at several levels, the main aim of this experiment was to test light-intensity-dependent influence of polyamine metabolism with or without exogenous polyamines. First, the effect of the duration of the daily illumination, then the effects of different light intensities (50, 250, and 500 μmol m–2 s–1) on the polyamine metabolism at metabolite and gene expression levels were investigated. In the second experiment, polyamine tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…Light intensity regulates free amino acid concentration at the transcriptional level, as shown by the increased expression of the genes related to Arg, Glu, Asp, and Ser metabolism. Since Arg is the precursor of polyamines, its light-induced accumulation activates their synthesis, as demonstrated with elevated putrescine and spermidine contents at higher PPFDs in leaves of wheat [ 155 ]. Polyamines, together with certain free amino acids (Pro, Glu, Cys), may have a role in the adaptation to changes in light conditions through their associations with the redox system.…”
Section: Light Intensity- and Spectrum-associated Adjustment Of Metab...mentioning
confidence: 99%
“…Light intensity regulates free amino acid concentration at the transcriptional level, as shown by the increased expression of the genes related to Arg, Glu, Asp, and Ser metabolism. Since Arg is the precursor of polyamines, its light-induced accumulation activates their synthesis, as demonstrated with elevated putrescine and spermidine contents at higher PPFDs in leaves of wheat [ 155 ]. Polyamines, together with certain free amino acids (Pro, Glu, Cys), may have a role in the adaptation to changes in light conditions through their associations with the redox system.…”
Section: Light Intensity- and Spectrum-associated Adjustment Of Metab...mentioning
confidence: 99%
“…PA treatments, namely PUT, SPD, and spermine (SPM) were applied at 0.3 mM concentration only under B, R, and P light regimes. In a previous study, the effects of these PA compounds were investigated under white light conditions at different light intensities [ 57 ]. In the present study PUT, SPD, and SPM treatments were applied only under B, R, and P regimes.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the effects of PA treatment under white light conditions was investigated under different light intensities, where it was demonstrated that in the leaves, light distinctly induced the PUT level and reduced the DAP content, which suggests that higher light conditions inhibit the terminal catabolism of higher PAs. In addition, exogenous PA treatments influenced the PA metabolism differently under different light intensities [ 57 ]. In the present study the effects of PUT, SPD, and SPM treatments were only investigated under B, R, and P regimes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations